Primary jugular foramen meningioma with unusual extensive bone destruction: case report and review of literature - Svjetlana Mujagić; Senada Sarihodžić; Haris Huseinagić; Jasmina Bećirović–Ibrišević; Zlatko Ercegović (Acta Medica Academica, 2010)
Jugular foramen meningiomas are exceedingly rare tumors of the fossa jugularis. These meningiomas are characterized by an invasive growth pattern with extensive skull base infiltration in all directions and by the mixed permeative-sclerotic appearance of the bone margins of the jugular foramen. We report an unusual case of a primary jugular foramen meningioma in a 30-year-old woman. The unenhanced high-resolution CT of the temporal bones revealed extensive bone destruction around the left jugular foramen as well as bone destruction of the basilar part of the left occipital bone without sclerosis. These findings are unusual for meningiomas and correspond more to glomus jugulare tumors. In the literature, we did not find a case similar to ours. Conclusion. MRI and CT imaging provide accurate distinction between meningioma and glomus tumors or schwannomas in most cases. From high-resolution CT scans, in the case where a permeative-destructive pattern is dominant, and with the absence of hyperostosis and bone thickening around the jugular foramen, the differential diagnosis between jugular foramen meningiomas and other tumors, especially glomus jugulare tumors, is difficult. In that case the correct diagnosis should be based on the MRI findings.